Violência nas relações de trabalho em uma instituição pública hospitalar - Aleilsa de Lima Paula (2022)
Violence in work relationships in a hospital is the subject of this dissertation. With the interest in understanding this phenomenon, we aim to identify the manifestation of violence in work relationships and, more specifically, to verify which types of violence most occur in this environment and to investigate the attitudes taken in the face of the experience with violence. For this purpose, in the foundations of the theory of contemporary society, in the foundations of the theory that approach this theme in society. The hospital institution by workers, regardless of the population of the Public Research Field, was composed of a hospital institution. From this population, a sample of one hundred and fifty-two professionals was highlighted. For data collection, end of violence, work and violence on reactions, a scale of sociodemographic data, end of violence, on work and reactions. Data analysis analysis and research program to the sociodemographic recognition and Violence at Work Scale were treated through the PS were grouped and highlighted for the text. The results confirm the presence of violence in work relationships, with moral harassment and verbal violence being the most common types of violence, although all types of violence investigated have been experienced by these professionals. They also found that workers react, when faced with the experience of violence, by making complaints to the police and hospital managers, seeking medical help, and also, in some cases, because they think that the situation will not be resolved by the institution, they decide not take action. It becomes necessary to approach the professionals of the order in society, through the creation of spaces for discussion in the work environment to eradicate the manifestation of violence caused by the form of management. Keywords: Violence, Work Relations, Critical Theory.